2015
DOI: 10.1021/jacs.5b11085
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Latent Carbocation Catalysis with Chiral Trityl Phosphate

Abstract: Stable carbocations such as tritylium ions have been widely explored as organic Lewis acid catalysts and reagents in organic synthesis. However, achieving asymmetric carbocation catalysis remains elusive ever since they were first identified over one century ago. The challenges mainly come from their limited compatibility, scarcity of chiral carbocations, as well as the extremely low barrier to racemization of chiral carbenium ions. We reported here a latent concept for asymmetric carbocation catalysis. In thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(31 citation statements)
references
References 136 publications
2
27
0
2
Order By: Relevance
“…2). It also should be noted that the proposed involvement of the covalently linked catalyst intermediates is consistent with the mechanistic proposals made by our group for the CPA-catalyzed reactions of acetals 27 and for the related transformation by Toste, 28 List, 29 Luo 30 and Ta-kasu 31 groups.…”
Section: Resultssupporting
confidence: 88%
“…2). It also should be noted that the proposed involvement of the covalently linked catalyst intermediates is consistent with the mechanistic proposals made by our group for the CPA-catalyzed reactions of acetals 27 and for the related transformation by Toste, 28 List, 29 Luo 30 and Ta-kasu 31 groups.…”
Section: Resultssupporting
confidence: 88%
“…Heteroaromatic aldehyde 5h formed an adduct with the tropylium ion at the nitrogen-centre and hence deactivated the reaction system. Aliphatic aldehydes also led to complicated reaction mixtures with some aldol and carbonyl-ene 18 byproducts.…”
Section: Resultsmentioning
confidence: 99%
“…With the modified trityl salt [ Me Tr] + [ 4 ] – in hand, we tested its catalytic activity in two representative Diels–Alder reactions and two Mukaiyama aldol additions . Franzén and co‐workers demonstrated that trityl cations are able to catalyze difficult Diels–Alder reactions involving cyclohexa‐1,3‐diene ( 14 ) as enophile in good yields .…”
Section: Resultsmentioning
confidence: 99%
“…Franzén had also tested an enantioselective counteranion‐directed Diels–Alder reaction of 14 with methacrolein ( 16 ) but could only observe cycloadduct 17 in trace amounts. [15b] Even though our catalyst enabled the desired reaction of 16 and 14 in moderate yield, there was no enantioinduction (Scheme , bottom). Diels–Alder reactions with anthracene as the enophile did not show any conversion.…”
Section: Resultsmentioning
confidence: 99%